Hepatocyte Growth Factor in Predialysis and Hemodialysis Chronic Kidney Disease Patients - Sarat Chandra Vulugundam; Vinapamula S Kiranmayi; P.V.L.N Srinivasa Rao; Siva Kumar Vishnubhotla (Saudi Journal of Kidney Diseases and Transplantation, 2022)
Chronic kidney disease (CKD) which is characterized by progressive loss of renal function and renal fibrosis is a worldwide public health problem. Hepatocyte growth factor (HGF) is a polypeptide that exhibits multiple functions including antifibrotic effects on kidneys. The present study was aimed at evaluating HGF levels and studying its association with markers of inflammation and oxidative stress in patients of predialysis and dialysis CKD. A total of 80 subjects including 20 healthy controls, 40 patients of CKD stage 1 to stage 5 (predialysis), and 20 CKD patients with end-stage renal disease on hemodialysis were recruited. HGF, high-sensitivity C-reactive protein (hsCRP), malondialdehyde (MDA), and ferric reducing ability of plasma (FRAP) were measured in all the subjects. HGF levels were significantly higher in all patients with CKD compared to controls. The levels were found to be lower in patients on dialysis than in the predialysis group; however, the difference was not statistically significant. hsCRP, MDA, and FRAP were significantly higher in all patients with CKD than in controls. HGF levels did not show a significant correlation with the markers studied. HGF levels were increased in response to renal injury in CKD patients. The levels were higher in predialysis patients of CKD than in CKD patients on dialysis. HGF levels may be used as an indicator of renal fibrosis in patients with CKD.